Overview of Flow Cytometry Techniques for Immunophenotyping in B-Cell Lymphoproliferative Disorders - B L T Balasuriya; C S Moonesinghe; S S N Fernando; T D C P Gunasekara; S Jayakody; C C Kariyawasan (Achievements and Challenges of Medicine and Medical Science Vol. 7, 2024)
B-cell lymphoproliferative disorders (BCLPDs) encompass a diverse range of neoplasms with immunophenotypic profiles. This review discusses the classification of BCLPDs based on flow cytometric immunophenotyping, focusing on markers such as CD5, and CD10. Key subtypes, including CLL, MCL, and DLBCL, are analyzed for diagnostic and prognostic insights. Advanced flow cytometry techniques aid in subtype differentiation, guiding personalized treatment approaches and improving outcomes. Global variations and diagnostic challenges are also highlighted, supporting a comprehensive understanding of BCLPDs.